Implementation of Spiritual Leadership at the Al-Hamra Kaibon Islamic Education Foundation - Ohib Muhibburrohman; Alsri Nurcahya; Rijal Firdaos (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to analyze the spiritual leadership style implemented in Islamic Boarding Schools. This research uses a qualitative method with a case study approach and literature study. Data were collected using observation, interviews, and literature documentation on four research topics; 1). The concept of spiritual leadership; 2). Characteristics of spiritual leadership; 3). Spirituality at work; and 4). Indicators and measurement tools of spiritual leadership. This study presents a basic understanding of spiritual leadership, including an in-depth understanding of the traits of spiritual leadership and indicator tools for measuring spiritual leadership. As well as the implementation of the theory already described. The conclusion of the result of this study is that spiritual leadership helps inspire its members to perform and achieve common goals. Spiritual leadership refers to the leadership character of the Prophet SWT. Indicators that can measure spiritual leadership are Shidiq, Amanah, Tabligh, and Fatonah. The implementation is the principal who has high integrity and honesty and has a sense of responsibility for what is entrusted by the Foundation environment and parents.